A Case of Epicardial Epidermoid Cyst in a Crested Porcupine - Alessia Mariacher; Valentina Galietta; Gianni Massai; Francesco Bruni; Giovanni Ragionieri; Claudia Eleni; Gianluca Fichi (Animals)
The crested porcupine (Hystrix cristata) is present in central Italy with an estimated population of 1800 individuals. Despite the local abundance, little data are available on the diseases affecting free-ranging individuals. We describe a case of an epidermoid cyst (EC) in a male adult porcupine found in the municipality of Sovicille, province of Siena (Tuscany). At necropsy, a firm rounded nodule was noted on the left ventricle wall. Histological examination revealed a cystic formation lined by stratified squamous epithelium. The cyst was filled with lamellar keratin, while hair shafts were not present. The adjacent epicardium was infiltrated by lymphoplasmacytic cells in reaction to the rupture of the cyst with the spilling of keratinaceous debris. The lesion was diagnosed as a ruptured epicardial epidermoid cyst. EC are most commonly found in the skin, both in human and animal patients, though infrequently, they can occur in any internal organ. Cardiac EC has not been reported in domestic animals, and this is the first report of EC in a wild animal species. Clinical veterinarians should consider the possibility of similar cardiac lesions in captive subjects since the long lifespan of these rodents could allow the growth of the cyst with the compression of the adjacent tissues.